Measuring the performance of urban healthcare services: results of an international experience. Issue 9 (14th August 2007) - García-Altés, Anna; Borrell, Carme; Coté, Louis; Plaza, Aina; Benet, Josep; Guarga, Alex
Abstract : The objective of this paper is to apply a framework for country-level performance assessment to the cities of Montreal, Canada, and Barcelona, Spain, and to use this framework to explore and understand the differences in their health systems. The UK National Health Service Performance Assessment Framework was chosen. Its indicators went through a process of selection, adaptation and prioritisation. Most of them were calculated for the period 2001–3, with data obtained from epidemiological, activity and economic registries. Montreal has a higher number of old people living alone and with limitations on performing one or more activities of daily life, as well as longer hospital stays for several conditions, especially in the case of elderly patients. This highlights a lack of mid-term, long-term and home care services. Diabetes-avoidable hospitalisation rates are also significant in Montreal, and are likely to improve following reforms in primary care. Efficient health policies such as generic drug prescription and major ambulatory surgery are lower in Barcelona. Rates of caesarean deliveries are higher in Barcelona, owing to demographics and clinical practice. Waiting times for knee arthroplasty are longer in Barcelona, which has triggered a plan to reduce them. In both cities, avoidable mortality and the prevalence of smoking have been identified as areas for improvement through preventive services. In conclusion, performance assessment fits perfectly in an urban context, as it has been shown to be a useful tool in designing and monitoring the accomplishment of programmes in both cities, to assess the performance of the services delivered, and for use in policy development.